There's a problem of which I know the solution but not the solving process:

$(\sqrt{x} + 7)(\sqrt{x} - 1) = \frac{105}{4}$

I'm convinced that up to:

$x + 6\sqrt{x} - 7 = \frac{105}{4}$

everything is correct.

But afterwards, I never seem to be able to get to the solution of $x = \frac{49}{4}$

How can this equation be solved?


Hint: Your equation can be rewritten as $$ (\sqrt{x})^2 + 6 \sqrt{x} -\frac{133}{4} = 0 $$ And so it is a quadratic equation in $\sqrt{x}$ that you can solve. So you find that $\sqrt{x}$ is equal to some number(s).

  • $\begingroup$ Are you sure that $-\frac{77}{4}$ is correct? $\endgroup$ – Miroslav Cetojevic May 15 '12 at 15:36
  • $\begingroup$ @MiroslavCetojevic oops, you are right. I edited the answer... $\endgroup$ – Thomas May 15 '12 at 15:39
  • $\begingroup$ I got $-\frac{133}{4}$, but otherwise it looks like this was the hint I needed. Thanks! $\endgroup$ – Miroslav Cetojevic May 15 '12 at 15:42
  • $\begingroup$ @MiroslavCetojevic, again: you are right. I am not good with numbers :) Glad that it helped though. $\endgroup$ – Thomas May 15 '12 at 15:43

Hint $\ $ Put $\:z = \sqrt{x},\:$ clear denominators and rearrange to obtain the quadratic equation$\:0 = 4 z^2 + 24 z - 133 = (2z-7)(2z+19),\:$ solvable by the quadratic formula, or the Rational Root Test or AC method, etc.

Alternatively, purely arithmetically, if it has rational root $\:\sqrt{x} = a/b\:$ in lowest terms then

$$ (\sqrt{x} +7)(\sqrt{x}-1)\ =\ \frac{a+7b}b\ \frac{a-b}{b}\ =\ \frac{3\cdot 5\cdot 7}4 $$

Since $\:b\:$ is coprime to $\:a,\:$ also $\:b\:$ is coprime to $\:a+7b,\ a-b,\:$ so we deduce $\:b = 2.\:$ Hence

$$ (a + 14)\:(a-2)\ =\ 3\cdot 5\cdot 7 $$

So we seek a factorization of $\:3\cdot 5\cdot 7\:$ whose factors differ by $\:16 = a+14-(a-2).\:$ Checking the few possible factorizations we find $\:21\cdot 5\:\Rightarrow\:a=7,\:$ and $\:-5\:(-21)\:\Rightarrow\:a = -19.\:$ Notice that this solution depends on uniqueness of factorization (as does RRT and the AC method).



  1. Multiply the given equation by $4$ to have integer coefficients only. (You may omit this step)
  2. Expand the LHS. $$4x+24\sqrt{x}-28=105.$$
  3. Isolate the term with a square root on one side. $$24\sqrt{x}=133-4x.$$
  4. Square both sides (this may introduce a new solution) and simplify. You get a quadratic equation. One of its two solutions satisfies the original equation. $$x_1=\frac{49}{4}.$$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.